UPAYA PERSONIL SEKOLAH DALAM MEWUJUDKAN SEKOLAH RAMAH ANAK DI SEKOLAH DASAR NEGERI 110 PEKANBARU - Nadhifa, Fairuza; Witri, Gustimal; Guslinda, Guslinda (Unversitas Katolik Santo Thomas, 2021)
This study aims to analyze the efforts of school personnel in realizing child-friendly schools at the 110 Pekanbaru State Elementary School. This type of research is qualitative research. This approach uses an approach that is holding data collection or the reality of the problem based on any research that has been explored or by the respondent. The data collected is in the form of written or spoken words from the people being observed. The results of the research on various plans that have been prepared later in alternative policies in which there are guidelines for developing programs and activities for the protection and education of children in the SRA. Thus, the formulation of the problem regarding the efforts of school personnel in realizing the 110 Pekanbaru public elementary school has been in accordance with the planning stages and has met the standard operating procedures for the Sekolah Ramah Anak program.